Be wary of “natural” therapy in gynecological surgery - Erian M; McLaren G (Dove Medical Press, 2013)
Mark Erian,1 Glenda McLaren21Department of Obstetrics and Gynaecology, University of Queensland, Royal Brisbane and Women's Hospital, Herston, 2Obstetrician and Gynaecologist, Mater Mothers Private Hospital, University of Queensland, Brisbane, QLD, AustraliaAbstract: It is estimated that more than 4 billion people throughout the world use natural herbs for some aspect of primary health care. These over-the-counter medications, commonly referred to as “complementary and alternative medicines,” despite their proposed health benefits, may have serious and potentially fatal side effects. This paper presents the case of a patient who underwent a gynecological operation and suffered heavy postoperative bleeding as a result of her taking large doses of oral raw garlic in the weeks prior to her operation and discusses the issue of patients’ perioperative intake of herbal supplements. To our knowledge, this is the first paper to demonstrate the relationship between a natural therapy and postoperative bleeding in gynecological surgery. The patient presented with severe postoperative bleeding following a routine, unremarkable vaginal hysterectomy. The bleeding required a multidisciplinary management intervention involving gynecological surgeons, general surgeons, oncology surgeons, hematologists, anesthetists, and intensive care unit specialists. After careful history taking (unfortunately, undertaken postoperatively), it was unanimously agreed that the postoperative hemorrhage was due to the patient’s excessive preoperative oral ingestion of raw garlic. The case and brief literature review presented in this paper concern an area of paucity in gynecological surgery and highlight the relationship between a commonly taken over-the-counter herbal medication and postoperative hemorrhage.Keywords: herbs, gynecological surgery, complementary medicines, alternative medicines, postoperative hemorrhage